PENGARUH PEMBERIAN JENIS PAKAN YANG BERBEDA TERHADAP MUTU GONAD CALON INDUK IKAN INGIR-INGIR (Mystus nigriceps) - Azmi Fadli; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted from January to March 2016 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine Science University of Riau Pekanbaru. The aim of this research was to evaluate suitable feed for the maturation of the gonad of bagrid catfish (Mystus nigriceps) reared with different feeding treatment (Commercial feed; cookle meat; soilworm(annelid) and chopped fresh fish. The research method used was Completely Randomized Design (CDR) with four treatments and three replications. The result showed that chopped fresh fish (Poecilia reticulata) and commercial dry food were the best food for maturating the fish gonad of bagrid catfish (Mystus nigriceps). Total fish reached matured stage IV was 16 fish (88,89%), gonad somatic index 9,06 %, relative fecundity 835 eggs/g fish, egg diameter 0,85 mm. The temperature range from 28 – 310C, pH 5 – 6, DO 5,7 – 6,8 ppm.Keyword: food types, Gonad maturation, bagrid catfish